Genetics of cryptorchidism and testicular regression - Elamo Heidi P; Virtanen Helena E; Toppari Jorma (Bailliere Tindall Ltd, 2022)
Cryptorchidism, i.e., undescended testis, is one of the most common genital malformations in newborn male babies. The birth rate of cryptorchidism varies from 1.6 to 9.0 %. Etiology of disrupted testicular descent is complex and predisposing causes include genetic, hormonal, environmental, lifestyle and maternal factors. Testicular descent occurs in two major steps and testicular hormones and normal function of hypothalamic–pituitary–testicular axis are important for normal descent. Several gene mutations are associated with syndromic cryptorchidism but they are rarely found in boys with isolated undescended testis.
Testicular regression can also cause an empty scrotum. Normal male genital phenotype indicates that the boy has had functioning testis during development. Torsion of the testis can cause testicular regression but in many cases the reason for vanishing testis remains elusive.
In this narrative review we discuss genetics of cryptorchidism and testicular regression.